The Ecto-5’-Nucleotidase/CD73 Inhibitor, α,β-Methylene Adenosine 5’-Diphosphate, Exacerbates Carrageenan-Induced Pleurisy in Rat - Caiazzo, Elisabetta; Morello, Silvana; Carnuccio, Rosa; Ialenti, Armando; Cicala, Carla (Frontiers in Pharmacology, 2019)
The ecto-5'-nucleotidase (ecto-5’NT/CD73) represents a crucial enzyme for endogenous adenosine generation. Several findings have shown that CD73 plays an important role in regulating vascular permeability and immune cell function. Adenosine 5'-(α,β-methylene) diphosphate (APCP) is a CD73 inhibitor, widely used as pharmacological tool to investigate the role of CD73/adenosine pathway in several in vitro and in vivo models, although it has been also shown to inhibit other ectoenzymes involved in adenosinergic pathway. Here, we evaluated the effect of APCP in the development of inflammation in carrageenan-induced pleurisy model. We found that treatment with APCP (400 μg/rat) significantly increased cell accumulation, exudate formation and pro-inflammatory cytokine content into the pleural cavity in the acute phase (4 h) of inflammation, with no differences in the sub-acute phase (72 h) except for the regulation of monocyte chemotactic protein-1 levels. In addition, cells collected by pleural lavage fluids of APCP - treated rats, 4 hours following carrageenan injection, showed increased ability to migrate in vitro, both in presence and in absence of N-formyl-L-methionyl-L-leucyl-L-phenylalanine as chemotactic stimulus, compared to cells obtained by control rats. Our results demonstrate that APCP exacerbates the early phase of carrageenan-induced pleurisy by controlling pleural effusion and polymorphonuclear migration in vivo and ex vivo. This effect is likely dependent upon CD73 inhibition, although an inhibitory effect of other ectoenzymes cannot be ruled out.